Isolating specific auxotrophic mutants of Mycobacterium smegmatis by using vancomycin. - Woodley, C L (1981)
After inducing mutagenesis with nitrosoguanidine, we used vancomycin enrichment in isolating auxotrophic mutants of Mycobacterium smegmatis. Compared with cycloserine and penicillin G, which are also cell wall inhibitors, vancomycin, with 24 h of exposure, produced less cell lysis and a greater reduction in viable cell numbers. With vancomycin enrichment, 13 specific auxotrophs were isolated after nitrosoguanidine-induced mutation, whereas only two mutants were isolated without enrichment.